A core-shell Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material and preparation method thereof

By preparing core-shell Ni/Co alloy @ nitrogen-doped carbon-based absorbing composite materials, the problems of complex synthesis and poor stability of existing absorbing materials are solved, and the effects of strong reflection loss and ultra-wide absorbing bandwidth are achieved, which is suitable for applications in different frequency bands.

CN114449877BActive Publication Date: 2025-03-11GUIZHOU UNIV +1

Patent Information

Application Number
CN202111309243.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-06
Publication Date
2025-03-11
Estimated Expiration
2041-11-06

Smart Images

  • Figure CN114449877B_ABST
    Figure CN114449877B_ABST
Patent Text Reader

Abstract

The present invention discloses a core-shell Ni / Co alloy @ nitrogen-doped carbon-based absorbing composite material and a preparation method thereof. First, a Ni / Co-MOF precursor is prepared by a simple hydrothermal reaction, and then a core-shell Ni / Co@C composite absorbing material is obtained by high-temperature treatment under an argon inert environment. The composite absorbing material has an optimal effective absorbing bandwidth (RL) value of 8.9 GHz at a thickness of 3.5 mm, and can reach 71.9 dB at a frequency of 8.9 GHz. The effective absorbing bandwidth of RL<10 is as high as 16 GHz, covering the S, C, X and Ku bands, and due to the formation of a carbon-wrapped nickel-cobalt core-shell structure, the material has good stability. The absorbing material prepared by the method of the present invention is environmentally friendly, has good stability, has a wide absorbing bandwidth, has high reflection loss, is simple in process, and is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electromagnetic absorbing materials, and more specifically, relates to a core-shell Ni / Co alloy@nitrogen-doped carbon-based absorbing composite material and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of microelectronics, 5G mobile technology, and civil and military precision equipment, electromagnetic pollution may endanger human health and even lead to information leakage. At present, people have made great efforts to obtain ideal electromagnetic wave absorbing materials with high, thin, wide and light properties. However, it is difficult for absorbing materials to simultaneously meet the requirements of a wide effective absorbing bandwidth (EAB) and a satisfactory reflection loss (RL).

[0003] Among the absorber materials studied, carbon-based materials with mainly electrical loss have been widely used due to their low density, good chemical stability, and high strength, but their poor magnetic properties lead to narrow EAB. CoNi alloys with mainly magnetic loss are considered to be an important electromagnetic wave absorber due to their high saturation magnetization, tunable morphology, and resolvable magnetic permeability in the high-frequency range. However, the skin effect, impedance mismatch, high density, easy oxidation, and easy agglomeration limit their electromagnetic wave absorption performance, so the effects of RL and EAB are not very ideal. Therefore, combining electrical loss and magnetic loss, using the synergistic effect to achieve impedance matching, and regulating the micromorphology to enhance dielectric loss are effective methods to improve RL.

[0004] The invention patent "Method for preparing nitrogen-doped porous carbon-coated hollow cobalt-nickel alloy composite absorbing material" (application publication number CN112743098A) discloses a method for preparing a nitrogen-doped porous carbon-coated hollow cobalt-nickel alloy composite absorbing material. Ni / Co alloy is synthesized by hydrazine hydrate, dopamine is polymerized in situ, and then a porous structure material is obtained by high-temperature calcination. The strongest reflection loss of the prepared absorbing material is about -47.1dB, and the maximum EAB is about 4.52GHz. Although the invention effectively enhances the reflection loss, its synthesis is complex and uses hydrazine hydrate, which is an easily made poison, and the absorption bandwidth is narrow, which limits its practical application. The invention patent "A method for preparing a cobalt-nickel alloy @ nitrogen-doped porous carbon composite microwave absorbing material" (application publication number CN112266766A) discloses a method for preparing a cobalt-nickel alloy @ nitrogen-doped porous carbon composite microwave absorbing material. A layer of COFs is grown on the alloy surface by precipitation polymerization. The obtained CoNi@COFs composite crystal is pyrolyzed to obtain a hollow cobalt-nickel alloy @ nitrogen-doped porous carbon composite microwave absorbing material with a core-shell structure. The maximum reflection loss (RL) of the invention reaches -55.4dB, and the EAB exceeds 5.12GHz. The easily made poison hydrazine hydrate is also used in the synthesis process. Summary of the invention

[0005] Aiming at the problems of complicated synthesis steps, poor stability, environmental unfriendliness, narrow effective absorbing bandwidth and poor absorbing strength of existing absorbing materials, the present invention proposes a method for preparing a core-shell Ni / Co alloy@nitrogen-doped carbon-based absorbing composite material.

[0006] The technical solution of the present invention is a method for preparing a core-shell Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material, comprising the following steps:

[0007] Step 1: Preparation of Ni / Co-MOF precursor:

[0008] The sodium salt and nicotinic acid are dissolved in deionized water and stirred to obtain solution A; nickel salt, cobalt salt and polyvinyl pyrrolidone are dissolved in deionized water and stirred to obtain solution B; solution B is slowly added to solution A and stirred, and then the mixed solution is transferred to an autoclave and reacted at 100-150° C. for 4-8 hours to obtain a Ni / Co-MOF precursor;

[0009] Step 2: Preparation of Ni / Co alloy @ nitrogen-doped carbon-based microwave absorbing composite material:

[0010] The Ni / Co-MOF precursor is pyrolyzed at 550-700°C in an argon environment for 0.5-2.5 hours at a heating rate of 2-8°C / min, and then cooled to obtain a Ni / Co alloy@nitrogen-doped carbon-based absorbing composite material Ni / Co@C with a core-shell structure.

[0011] The mass ratio of the sodium salt, nicotinic acid, nickel salt and cobalt salt is 1:1:2:1-4:5:6:4.

[0012] The sodium salt is sodium acetate, and the nickel salt is nickel nitrate.

[0013] The cobalt salt is cobalt nitrate.

[0014] Preferably, the reaction conditions in step 1 are temperature 120° C. and time 6 h.

[0015] In step 2, preferably, the heating rate is 2°C / min, the holding time is 2h, and the calcination temperature is 600°C.

[0016] The application of the core-shell Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material in microwave absorbers.

[0017] A Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material (Ni / Co@C) with a core-shell structure was mixed with paraffin to obtain a Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material microwave absorber.

[0018] The mass ratio of the Ni / Co alloy@nitrogen-doped carbon-based wave-absorbing composite material to paraffin is 2:1-4.

[0019] Beneficial effects of the invention: The invention relates to a method for preparing an absorbing material with simple process, environmental friendliness, strong reflection loss and ultra-wide absorption bandwidth, which includes two processes: preparation of precursor Ni / Co-MOF and calcination treatment. By changing the calcination temperature and purposefully regulating the Ni / Co@C morphology, a nano-sized uniform carbon-wrapped Ni / Co alloy core-shell absorbing material is obtained, which has high reflection loss (RL) and wide effective absorption bandwidth (EAB). The details are as follows:

[0020] 1. Nicotinic acid, the organic ligand used in the precursor Ni / Co-MOF, is non-toxic. The solvent used in the synthesis is water. No waste liquid or waste residue is produced, which is completely environmentally friendly.

[0021] 2. The present invention pre-synthesizes Ni / Co-MOF and obtains a carbon-based composite material with uniform alloy distribution through pyrolysis, thereby overcoming the disadvantage of high density of pure alloy and reducing the weight of the absorbing material.

[0022] 3. The present invention calcined the precursor Ni / Co-MOF to obtain an absorbing material with carbon as the shell and Ni / Co as the core. Carbon provides electrical loss, Ni / Co alloy provides magnetic loss, and electromagnetic loss works together to optimize impedance matching and improve absorbing performance. In addition, the Ni / Co alloy is tightly wrapped by the carbon layer, which prevents oxidation of the alloy and achieves good stability. The nanoscale microscopic core-shell structure realizes multiple reflections of electromagnetic waves and increases dielectric loss.

[0023] 4. The core-shell Ni / Co alloy @ nitrogen-doped carbon-based absorbing composite material of the present invention simultaneously meets the requirements of strong absorbing ability (RL) and wide effective absorbing bandwidth (EAB). At a frequency of 8.9 GHz, the optimal RL value can reach -71.9 dB, and the effective absorbing bandwidth of RL<-10 is as high as 16 GHz, covering the S, C, X and Ku bands. By adjusting the thickness, the prepared absorbing material can be applied to different fields in the 2-18 GHz frequency band.

[0024] 5. The process of the present invention is simple, environmentally friendly, the material is corrosion-resistant, the production cost is low, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is the X-ray diffraction (XRD) pattern of Ni / Co@C-600 of the present invention;

[0026] Figure 2 This is a SEM image of the precursor Ni / Co-MOF of the present invention;

[0027] Figure 3This is the SEM image of Ni / Co@C-600 of the present invention;

[0028] Figure 4 TEM image of Ni / Co@C-600 of the present invention;

[0029] Figure 5 This is the microwave absorption performance diagram of Ni / Co@C-600 composite material. DETAILED DESCRIPTION

[0030] Example 1

[0031] (1) Preparation of Co / Ni-MOF precursor

[0032] 1.21g CH3COONa·3H2O and 1.22g nicotinic acid were dissolved in 100ml deionized water and stirred for 30 minutes to obtain solution A. At the same time, 2.1g Ni(NO3)2·6H2O, 1.2g Co(NO3)2·6H2O and 1.1g polyvinyl pyrrolidone (PVP) were dissolved in 100ml deionized water and stirred for 30 minutes to obtain solution B. Solution B was slowly added to solution A and stirred for 30 minutes. Then the mixed solution was transferred to a 250ml polytetrafluoroethylene stainless steel autoclave and reacted at 120℃ for 6 hours. After cooling naturally to room temperature, a gray-blue precipitate was obtained, which was rinsed with deionized water 3 times and vacuum dried at 60℃ for 24 hours to obtain the CoNi-MOF precursor.

[0033] (2) Preparation of Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite materials

[0034] The Ni / Co-MOF precursor was placed in a crucible and pyrolyzed at 550°C for 2 hours in an argon environment at a heating rate of 2°C / min, and then naturally cooled to obtain a Ni / Co alloy@nitrogen-doped carbon-based absorbing composite material (Ni / Co@C-550).

[0035] (3) Ni / Co@C-550 microwave absorption performance test

[0036] The composite material is mixed with paraffin to obtain a Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material microwave absorber, wherein the mass ratio of the Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material to the paraffin is 2:3.

[0037] The electromagnetic parameters are measured using a vector network analyzer. According to the transmission line theory, the reflection loss of the material to electromagnetic waves is calculated using the following equation using the complex dielectric constant and complex magnetic permeability at a given frequency and the thickness of the absorbing material.

[0038]

[0039]

[0040] The optimal RL value of the absorbing material reaches -8.8dB when the frequency is 7.1GHz and the thickness is 5.5mm.

[0041] Example 2

[0042] (1) Preparation of Co / Ni-MOF precursor

[0043] CH3COONa·3H2O is 2.42g, nicotinic acid is 2.44g, Ni(NO3)2·6H2O is 3.15g, Co(NO3)2·6H2Og is 2.4, and the rest is the same as Example 1.

[0044] (2) Preparation of core-shell Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composites

[0045] The Ni / Co-MOF precursor was placed in a crucible and pyrolyzed at 600°C for 2 hours in an argon environment at a heating rate of 2°C / min, and then naturally cooled to obtain a Ni / Co alloy@nitrogen-doped carbon-based absorbing composite material (Ni / Co@C-600) with a core-shell structure.

[0046] (3) Ni / Co@C-600 microwave absorption performance test

[0047] The absorbing material used is the composite material prepared in Example 2, and the rest is the same as Example 1. It is measured that when the frequency of the absorbing material is 8.9 GHz and the thickness is 3.5 mm, the optimal RL value can reach -71.9 dB, and the effective absorbing bandwidth of RL<-10 is as high as 16 GHz, covering the S, C, X and Ku bands.

[0048] Example 3

[0049] (1) Preparation of CoNi-MOF precursor

[0050] CH3COONa·3H2O is 3.63g, nicotinic acid is 3.66g, Ni(NO3)2·6H2O is 4.2g, Co(NO3)2·6H2Og is 3.6, and the rest is the same as Example 1.

[0051] (2) Preparation of Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite materials

[0052] The Ni / Co-MOF precursor was placed in a crucible and pyrolyzed at 650°C for 2 hours in an argon environment with a heating rate of 2°C / min, and then naturally cooled to obtain a Ni / Co alloy@nitrogen-doped carbon-based absorbing composite material (Ni / Co@C-650).

[0053] (3) Ni / Co@C-650 microwave absorption performance test

[0054] The absorbing material used is the composite material prepared in Example 3, and the other parts are the same as in Example 1. It is measured that when the frequency of the absorbing material is 16.4 GHz and the thickness is 2 mm, the optimal RL value can reach -66.3 dB.

[0055] Example 4

[0056] (1) Preparation of CoNi-MOF precursor

[0057] CH3COONa·3H2O is 4.84g, nicotinic acid is 6.1g, Ni(NO3)2·6H2O is 6.3g, Co(NO3)2·6H2Og is 4.8, and the rest is the same as Example 1.

[0058] (2) Preparation of Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite materials

[0059] The Ni / Co-MOF precursor was placed in a crucible and pyrolyzed at 700 °C for 2 h in an argon environment at a heating rate of 2 °C / min, and then naturally cooled to obtain a Ni / Co alloy @ nitrogen-doped carbon-based microwave absorbing composite material (Ni / Co@C-700).

[0060] (3) Ni / Co@C-700 microwave absorption performance test

[0061] The absorbing material used is the composite material prepared in Example 4, and the other parts are the same as in Example 1. It is measured that the optimal RL value of the absorbing material can reach -9dB when the frequency is 15.1GHz and the thickness is 1.5mm.

[0062] Analysis of the drawings in the specification

[0063] Figure 1 This is the X-ray diffraction pattern of CoNi@C-600. The XRD pattern shows three peaks at 44.5°, 51.8° and 76.3°, corresponding to the (111), (200) and (220) planes of cubic fcc-Ni (JCPDS No.04-0850) and fcc-Co (JCPDS No.15-0806). A weak broad peak appears at 2θ=24.5°, which is attributed to the typical carbon (002) plane. There are no extra peaks in the figure, indicating that under the protection of an inert atmosphere, Ni 2+ / Co 2+ The ions are completely reduced by carbon to form the alloy Ni / Co.

[0064] from Figure 2 It can be seen that the surface of the precursor Ni / Co-MOF is smooth. Figure 3 The SEM image shows that the surface of Ni / Co@C-600 becomes rough after calcination and carbonization, and the surface is covered with nanospheres. Figure 4The TEM image shows that Ni / Co@C-600 has a core-shell structure. Figure 5 This is the reflection loss spectrum of Ni / Co@C-600. The figure shows that at a thickness of 3.5mm and a frequency of 8.9GHz, the optimal effective absorption bandwidth (RL) value can reach -71.9dB.

Claims

1. A method for preparing a core-shell Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material, characterized in that: The following steps are involved: Step 1: Preparation of Ni / Co-MOF precursor: The sodium salt and nicotinic acid are dissolved in deionized water and stirred to obtain a solution A; the nickel salt, cobalt salt and polyvinyl pyrrolidone are dissolved in deionized water and stirred to obtain a solution B; the solution B is slowly added to the solution A and stirred, and then the mixed solution is transferred to an autoclave, reacted at 100-150° C. for 4-8 hours, and then a Ni / Co-MOF precursor is obtained; the mass ratio of the sodium salt, nicotinic acid, nickel salt and cobalt salt is: 1:1:2:1-4:5:6:4; Step 2: Preparation of Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material: The Ni / Co-MOF precursor is pyrolyzed at 550-700°C in an argon environment for 0.5-2.5 hours at a heating rate of 2-8°C / min, and then cooled to obtain a Ni / Co alloy@nitrogen-doped carbon-based absorbing composite material Ni / Co@C with a core-shell structure.

2. The method for preparing a core-shell Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material according to claim 1, characterized in that: The sodium salt is sodium acetate, and the nickel salt is nickel nitrate.

3. The method for preparing a core-shell Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material according to claim 1, characterized in that: The cobalt salt is cobalt nitrate.

4. The method for preparing a core-shell Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material according to claim 1, characterized in that: The reaction conditions in step 1 are temperature 120° C. and time 6 h.

5. The method for preparing a core-shell Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material according to claim 1, characterized in that: In step 2, the heating rate is 2°C / min, the holding time is 2h, and the calcination temperature is 600°C.

6. Use of the core-shell Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material prepared by the preparation method according to any one of claims 1 to 5 in a microwave absorber.

7. The use according to claim 6, characterized in that: A Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material (Ni / Co@C) with a core-shell structure was mixed with paraffin to obtain a Ni / Co alloy@nitrogen-doped carbon-based microwave absorbing composite material microwave absorber.

8. The use according to claim 7, characterized in that: The mass ratio of the Ni / Co alloy@nitrogen-doped carbon-based wave-absorbing composite material to paraffin is 2:1-4.

Citation Information

Patent Citations

  • Preparation method of cobalt-nickel alloy and nitrogen-doped porous carbon composite microwave absorbing material

    CN112266766A

  • Preparation method of nitrogen-doped porous carbon coated hollow cobalt-nickel alloy composite wave-absorbing material

    CN112743098A

  • Iron-cobalt-nickel alloy / carbon / graphene ultrathin wave-absorbing material and preparation method thereof

    CN113088252A

  • Core-Shell Composites for Shielding Electromagnetic Interference and Method for Preparing the Same

    KR102273260B1

Cited By

  • Composite microwave absorbing material and preparation method and application thereof

    CN122807073A